The night woods - Munier, Paula (Munier, Paula. Mercy Carr mystery., 2024)
"The sixth Mercy Carr Mystery in which Mercy and Elvis must prove the innocence of a new friend accused of murder. Record snow and sleet and rain are pummeling Vermont and a wild boar has escaped from an exclusive hunting club nearby-but that won't stop a very pregnant and very bored Mercy Carr from hiking her beloved woods with her loyal dog Elvis. She's supposed to be decorating the nursery and helping her mother plan the baby shower, but she'd much rather be playing Scrabble with Homer Grant, a word-loving, shotgun-toting hermit living deep in the forest. But when she and Elvis drop by Homer's cabin for their weekly game, they arrive to find an unknown dead man-and no sign of Homer. As they search the woods, Mercy discovers a patch of devastation that could only be left behind by wild boar. She's relieved when Elvis tracks Homer, injured but alive. But Homer's troubles are far from over, as he's still the number one suspect and he remembers nothing of the attack. When another corpse with a link to Homer is found, Mercy is determined to help her friend, an effort complicated by the unexpected arrival of her young cousin Tandie, sent by Mercy's mother to keep an eye on her until the baby is born. As the floods worsen, Troy and Susie Bear are called out with all the other first responders, and Mercy finds herself alone at Grackle Tree Farm with a concussed Homer, Tandie, and Elvis. As waters rise and the wild boar rampages, Mercy realizes that the murderer is out there ready to strike again, this time much closer to home"--